Determinan Pengaruh Kekurangan Energi Kronis di Wilayah Pertanian, Desa Tangsil Wetan, Kabupaten Bondowoso - Salsabila, Shabrina; Syahda, Veda Vania; Zahari, Najma Haris (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2025)
Chronic Energy Deficiency (CED) in pregnant women is one of the public health problems that has an impact on increasing the risk of pregnancy complications, childbirth, and maternal and infant mortality. This study aims to analyze the factors that influence the incidence of CED in pregnant women in the agricultural area of Tangsil Wetan Village, Bondowoso Regency. The study used an observational analytical design with a case control study approach, involving 40 pregnant women respondents with a total sampling technique. Primary data were collected through interviews using questionnaires, then analyzed using the Fisher's Exact test and Odds Ratio (OR) calculation using the SPSS application. The results showed a significant relationship between age, education level, economic status, pregnancy spacing, antenatal care (ANC) visits, knowledge of CED, and animal protein consumption with the nutritional status of pregnant women. Pregnant women with an age at risk, low education level, low economic status, close pregnancy spacing, less ANC visits, low knowledge of CED, and infrequent consumption of animal protein have a higher risk of experiencing CED. These findings emphasize the need for efforts to prevent CED through increasing nutrition education, routine pregnancy check-ups, and community-based interventions to improve the nutritional status of pregnant women in agricultural areas.